Composing the Music of Africa Composition, Interpretation and Realisation - Agawu, V. Kofi (Oxford University Press, Oxford, 2000)
RESUMEN: Editado por Malcom Floyd, "Studies in Ethnomusicology". Ashgate, Aldershot, 1999.